The Complementarity of Riwayah, Tarbawi, and Contextual Interpretation in Character Education: A Comparative Study of the Story of Prophet Noah in Q.S. Hud 25–49 and Q.S. Noah 1–28: Komplementaritas Tafsir Riwayat, Tarbawi, dan Kontekstual dalam Pendidikan Karakter: Kajian Muqaran atas Kisah Nabi Nuh dalam QS. Hud 25-49 dan QS. Nuh 1-28 - Ahmad Ajik Nur Fata Mubarok (Senarai: Journal of Islamic Heritage and Civilization, 2026)
Character education programs in Indonesia have not yet produced satisfactory outcomes, while the Qur'anic narratives of the Prophet, arguably the most authentic indigenous source for character formation in the Islamic tradition, remain rarely examined through systematic exegetical methods. Rather than treating this narrative as settled pedagogical material, this study approaches it as a problem in the history of tafsir reception: how have successive exegetical traditions constructed, and continue to construct, moral meaning out of the same Qur'anic narrative unit, and what does the pattern of agreement and disagreement among them reveal about the epistemic status of the values they extract? The study examines the story of Prophet Noah across QS. Hud (25-49) and QS. Nuh (1-28) through a comparative exegesis (tafsir muqaran) of three exegetical works representing distinct interpretive traditions and historical moments: Ibn Kathir's Tafsir al-Qur'an al-'Azim (fourteenth-century Sunni tafsir bi al-ma'tsur), Anwar al-Baz's al-Tafsir al-Tarbawi lil-Qur'an al-Karim (contemporary Egyptian tarbawi exegesis), and M. Quraish Shihab's Tafsir al-Misbah (contemporary Indonesian contextual-adabi exegesis). Using an explicit unit-of-analysis and coding procedure applied to the two narrative segments, the study finds that the three exegetes are complementary rather than contradictory on four substantive points while diverging productively on questions of emphasis, audience, and epistemic warrant. Nine character-education values emerge from this comparison and are organized within Ahmad Tafsir's insan kamil framework across three dimensions, the heart (al-iman al-rasikh, al-shabr al-tarbawi, al-ikhlas al-tarbawi, al-tawakkul al-fa'al), the intellect (al-hikmah al-hiwariyyah, tanwi' al-asalib, al-mas'uliyyah al-tarbawiyyah), and the physical-social dimension (al-qiyadah al-khuluqiyyah, al-'adl al-ijtima'i), with al-iman al-rasikh functioning as the value on which the study's data most consistently converge. The article closes by distinguishing which of these nine terms are drawn directly from al-Baz's text, which are the author's own analytical constructions built on al-Baz's reading, and which recur independently across all three exegetes.